Reducing carbon emission commitment constraints of Chinese passenger vehicle manufacturers through life cycle management - Keke Ji; Qing Yang; Zipeng Lin; Yuping Li; Xin Sun; Jiaxin Yu; Xingxing Liu; Liang Dong (Sustainable Production and Consumption, 2026)

Improvement of a Large-Scale Circulation Simulation in an Ocean-Sea Ice Model with High Resolution - Yiwen Li; Hailong Liu; Pengfei Lin; Mengrong Ding; Zipeng Yu (Advances in Atmospheric Sciences, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

An assessment on short-term sea surface temperature forecast in China seas based on a global eddy-resolving dynamical forecast system - Huan Xu; Pengfei Lin; Xuhua Cheng; Hailong Liu; Weipeng Zheng; Zipeng Yu; Yongqiang Yu; Yiwen Li; Tao Zhang (Journal of Oceanology and Limnology, 2026)

Evaluation of the multi-scale variability of ocean bottom pressure in a global ocean general circulation model - Jiahui Bai; Jingwei Xie; Zipeng Yu; Jiangfeng Yu; Hailong Liu; Fan Yang; Pengfei Lin; Tao Zhang; Chunxiang Shi; Yun Xiao (Acta Oceanologica Sinica, 2026)

Engineering scaffold-cell interactions for cultured meat: mechanisms, materials, and emerging AI-driven strategies - Linzi Li; Yijun Zhang; Zipeng Xu; Shuai Yan; Nuo Yan; Cong Zhao; Yabin Niu; Shijie Ding; Guanghong Zhou; Lin Chen; Xianchao Feng (Trends in Food Science & Technology, 2025)

A knowledge graph approach to global nickel mining operations: Patterns and geopolitical insights - Zipeng Lin; Peng Wang; Linbin Tang; Francesca Larosa; Yongguang Zhu; Paul Ekins; Wei-Qiang Chen (Sustainable Production and Consumption, 2025)

The impact of wave-induced mixing on the simulation of the upper mixed layer in climate models - Yujie Jing; Jian Sun; Rui Li; Kejian Wu; Zipeng Yu; Pengfei Lin; Xianghui Dong; Alexander V. Babanin (Ocean Modelling, 2025)

Forecasting Ocean Mesoscale Eddies in the Northwest Pacific in a Dynamic Ocean Forecast System - Jiakang Zhang; Hailong Liu; Mengrong Ding; Yao Meng; Weipeng Zheng; Pengfei Lin; Zipeng Yu; Yiwen Li; Pengfei Wang; Jian Chen (Journal of Marine Science and Engineering, 2025)
The LICOM Forecast System (LFS), a global eddy-resolving ocean forecasting system, provides 1–15-day forecasts of ocean mesoscale eddies (OMEs). This study conducts a comparative analysis of the forecast results against observational data, thereby evaluating the performance of the LFS. Results show that LFS underestimates the number of eddies by ~10% and their amplitude by ~30%, while overestimating eddy radius by ~5% and velocity by ~25%. Forecasted eddies are matched on a one-to-one basis with observed eddies based on distance, ensuring that those forecasted eddies that can locate corresponding counterparts in the observational dataset yield accurate forecasts. The outcomes reveal that the LFS successfully forecasts 63% of the eddies in the NWP. The characteristics of these accurately forecasted eddies are delineated. The findings indicate that eddies with greater amplitudes are more likely to be accurately predicted. Additionally, we further scrutinized the correlation between eddy attributes and forecast performance, revealing that with an increase in amplitude or a decrease in velocity, the LFS produces forecasts with improved locational accuracy. The mean forecast error in eddy position is 79.94 km for a 1-day lead time, which decreases to 70.97 km for eddies with amplitudes exceeding 1 cm and velocities below 1 km/day.

The simulation of the South China Sea by the variable resolution version of the global ocean general circulation model LICOM3.0 - Jiangfeng Yu; Jingwei Xie; Hailong Liu; Pengfei Lin; Zipeng Yu; Jiahui Bai (Ocean Modelling, 2025)

High-affinity uric acid clearance based on motile β-CD/F-127 polyrotaxane microspheres for enhanced diabetic wound repair - Xinlin Jiang; Zipeng Wu; Xiaoru Tan; Yichen Lin; Hui Xing; Yinglin Xuan; Dong Ma; Xin Cui (Carbohydrate Polymers, 2025)

Transportation development paths in 30 provinces of China in the context of carbon quota allocation - Keke Ji; Qing Yang; Liang Dong; Zipeng Lin; Kaili Ji; Ting Zhang; Xingxing Liu (Journal of Transport Geography, 2025)

Impacts of model resolution on the simulation of sea-level variability by a global ocean-sea ice model - Yaqi Wang; Hailong Liu; Zipeng Yu; Pengfei Lin; Mengrong Ding (Climate Dynamics, 2025)

Can macroprudential policy rail for green innovation? Evidence from Chinese energy enterprises - Xin Lin; Zipeng Li; Suxu Lin (Environment, Development and Sustainability, 2024)

Nonlinear impact of automobile industry agglomeration on CO2 emission: Incorporating urban characteristics in China - Keke Ji; Qing Yang; Hailong Zhao; Mingnan Zhao; Lei Wang; Kaili Ji; Xingxing Liu; Zipeng Lin; Yandi Zheng (Journal of Cleaner Production, 2024)

Quantifying the Role of the Eddy Transfer Coefficient in Simulating the Response of the Southern Ocean Meridional Overturning Circulation to Enhanced Westerlies in a Coarse-resolution Model - Yiwen Li; Hailong Liu; Pengfei Lin; Eric P. Chassignet; Zipeng Yu; Fanghua Wu (Advances in Atmospheric Sciences, 2024)

Tide simulation in a global eddy-resolving ocean model - Zhiwei Tian; Caixia Wang; Zipeng Yu; Hailong Liu; Pengfei Lin; Zhuhua Li (Acta Oceanologica Sinica, 2024)

Evaluating westward and eastward propagating mesoscale eddies using a 1/10° global ocean simulation of CAS-LICOM3 - Mengrong Ding; Hailong Liu; Pengfei Lin; Yao Meng; Zipeng Yu (Ocean Modelling, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

Simulation of the climate and ocean circulations in the Middle Miocene Climate Optimum by a coupled model FGOALS-g3 - Jilin Wei; Hailong Liu; Yan Zhao; Pengfei Lin; Zipeng Yu; Lijuan Li; Jinbo Xie; Anmin Duan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

An Assessment of Marine Heatwaves in a Global Eddy-Resolving Ocean Forecast System: A Case Study around China - Yiwen Li; Juan Liu; Pengfei Lin; Hailong Liu; Zipeng Yu; Weipeng Zheng; Jinlei Chen (Journal of Marine Science and Engineering, 2023)
Marine heatwaves (MHWs) are becoming increasingly frequent and intense around China, impacting marine ecosystems and coastal communities. Accurate forecasting of MHWs is crucial for their management and mitigation. In this study, we assess the forecasting ability of the global eddy-resolving ocean forecast system LICOM Forecast System (LFS) for the MHW events in October 2021 around China. Our results show that the 1-day lead forecast by the LFS accounts for up to 79% of the observed MHWs, with the highest skill during the initial and decay periods. The forecasted duration and intensity of the MHW event are consistent with observations but with some deviations in specific regions of the Yellow and South China seas. A detailed analysis of the heat budget reveals that the forecasted shortwave radiation flux is a key factor in the accuracy of the forecasted MHW duration and intensity. The oceanic dynamic term also greatly contributes to the accuracy in the southern Yellow Sea. In addition, the increasing bias of the forecasted duration and intensity with lead time are mainly caused by the underestimated shortwave radiation. Our findings suggest that improving the accuracy of oceanic dynamic processes and surface radiation fluxes in the LFS could be a promising direction to enhance the forecasting ability of marine extreme events such as MHWs.

Quantifying tree canopy coverage threshold of typical residential quarters considering human thermal comfort and heat dynamics under extreme heat - Yingnan Li; Dongli Lin; Yuhan Zhang; Zipeng Song; Xiaohan Sha; Siqi Zhou; Cen Chen; Zhaowu Yu (Building and Environment, 2023)

Exploring the global trade networks of the tungsten supply chain: Insights into the physical and monetary mismatch among countries - Linbin Tang; Peng Wang; Zijie Ma; Stefan Pauliuk; Wei‐Qiang Chen; Tao Dai; Zipeng Lin (Journal of Industrial Ecology, 2023)
International trade is essential to bridge the imbalance between supply and demand of materials along with different nations effectively, especially for critical raw materials such as tungsten that are highly geographically unequally distributed. However, the international trade flows and their complex networks that link those participating nations have remained largely unexplored, which leads to inexplicable concerns for materials' criticality and their supply risks. By integrating the material flow analysis and the complex network analysis, this study traces the global trade flows of tungsten in various forms ranging from primary products to scrap among 223 countries and regions annually from 2000 to 2018 and explores the evolution of participating countries' role involved in international trade networks from both physical and monetary perspectives. We found that (1) there are ∼2673 thousand metric tons of tungsten feeding into supply chains globally during the 19 years, and about 96% of tungsten resources are re‐allocated from Asia to the high‐income regions; (2) the high‐income countries gain the potential benefits from both the resources and economic perspectives and they import 72% of tungsten resources in the form of primary and semi‐products from developing countries, meanwhile earning 87% of global tungsten trade value by exporting tungsten metal products with high value‐added back to those tungsten resources suppliers. Under the growing national interconnections of global tungsten trade networks, this study urges more cooperative actions and targeted supply chain management among the participating countries to secure the tungsten supply and sustainability of the global tungsten cycle.

Construction and evaluation of curcumin upconversion nanocarriers decorated with MnO2 for tumor photodynamic therapy - Xinru Chen; Quandong Li; Zipeng Huang; Wen Lin; Yan Ma (Drug Delivery and Translational Research, 2022)

Uncertainty in Atlantic Multidecadal Oscillation derived from different observed datasets and their possible causes - Bowen Zhao; Pengfei Lin; Aixue Hu; Hailong Liu; Mengrong Ding; Zipeng Yu; Yongqiang Yu (Frontiers in Marine Science, 2022)
As a leading mode of sea surface temperature (SST) variability over the North Atlantic in both observations and model simulations, the Atlantic Multidecadal Oscillation (AMO) can have a substantial influence on regional and global climate. By using Low-Frequency Component Analysis, we explore the uncertainties of the resulting AMO indices and the corresponding spatial patterns derived from three observational SST datasets. We found that the known coherent spatial pattern of the AMO at the basin scale over the North Atlantic appears in two out of the three datasets. Further analysis indicates that both the warming trend and the different techniques used to construct these observed gridded SSTs contribute to the AMO’s spatial coherence over the North Atlantic, especially during periods of sparse data sampling. The SST in the Extended Reconstructed SST dataset version 5 (ERSSTv5), changes from being systematically below the other datasets during the dense sampling periods on either side of the Second World War (WWII), to systematically above the other datasets during WWII, thereby introducing an artificial 10–20-year variability that affects the AMO’s spatial coherence. This coherence in the AMO’s spatial pattern is also affected by bias adjustment in ERSSTv5 at relative cool (i.e., non-summer) seasons, and by the heterogeneous North Atlantic warming pattern. The different AMO patterns can induce the different effects of wind, surface heat fluxes, and then drive ocean circulation and its heat transport convergence, especially for some seasons. For AMO indices, both the different detrending methods and different observational data result in uncertainty for the period 1935–1950. Such SST uncertainty is important to detect the relative role of the atmosphere and ocean in shaping the AMO.

The Super-large Ensemble Experiments of CAS FGOALS-g3 - Pengfei Lin; Bowen Zhao; Jilin Wei; Hailong Liu; Wenxia Zhang; Xiaolong Chen; Jie Jiang; Mengrong Ding; Wenmin Man; Jinrong Jiang; Xu Zhang; Yuewen Ding; et al. (Advances in Atmospheric Sciences, 2022)
A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) and an experiment (2015–99) under the very high greenhouse gas emissions Shared Socioeconomic Pathway scenario (SSP5-8.5). The dataset includes monthly and daily temperature, precipitation, and other variables, requiring storage of 275 TB. Additionally, the surface air temperature (SAT) and land precipitation simulated by the FGOALS-g3 super-large ensemble have been validated and projected. The ensemble can capture the response of SAT and land precipitation to external forcings well, and the internal variabilities can be quantified. The availability of more than 100 realizations will help researchers to study rare events and improve the understanding of the impact of internal variability on forced climate changes.

Eddy-resolving Simulation of CAS-LICOM3 for Phase 2 of the Ocean Model Intercomparison Project - Yiwen Li; Hailong Liu; Mengrong Ding; Pengfei Lin; Zipeng Yu; Yongqiang Yu; Yao Meng; Yunlong Li; Xiaodong Jian; Jinrong Jiang; Kangjun Chen; Qian Yang; et al. (Advances in Atmospheric Sciences, 2020)
A 61-year (1958–2018) global eddy-resolving dataset for phase 2 of the Ocean Model Intercomparison Project has been produced by the version 3 of Chinese Academy of Science, the State Key Laboratory of Numerical Modeling for Atmospheric Sciences and Geophysical Fluid Dynamics/Institute of Atmospheric Physics (LASG/IAP) Climate system Ocean Model (CAS-LICOM3). The monthly and a part of the surface daily data in this study can be accessed on the Earth System Grid Federation (ESGF) node. Besides the details of the model and experiments, the evolutions and spatial patterns of large-scale and mesoscale features are also presented. The mesoscale features are reproduced well in the high-resolution simulation, as the mesoscale activities can contribute up to 50% of the total SST variability in eddy-rich regions. Also, the large-scale circulations are remarkably improved compared with the low-resolution simulation, such as the climatological annual mean SST (the RMSE is reduced from 0.59°C to 0.47°C, globally) and the evolution of Atlantic Meridional Overturning Circulation. The preliminary evaluation also indicates that there are systematic biases in the salinity, the separation location of the western boundary currents, and the magnitude of eddy kinetic energy. All these biases are worthy of further investigation.

FGOALS-g3 Model Datasets for CMIP6 Flux-Anomaly-Forced Model Intercomparison Project - Yaqi Wang; Zipeng Yu; Pengfei Lin; Hailong Liu; Jiangbo Jin; Lijuan Li; Yanli Tang; Li Dong; Kangjun Chen; Yiwen Li; Qian Yang; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)
The Flux-Anomaly-Forced Model Intercomparison Project (FAFMIP) is an endorsed Model Intercomparison Project in phase 6 of the Coupled Model Intercomparison Project (CMIP6). The goal of FAFMIP is to investigate the spread in the atmosphere-ocean general circulation model projections of ocean climate change forced by increased CO 2 , including the uncertainties in the simulations of ocean heat uptake, global mean sea level rise due to ocean thermal expansion and dynamic sea level change due to ocean circulation and density changes. The FAFMIP experiments have already been conducted with the Flexible Global Ocean-Atmosphere-Land System Model, gridpoint version 3.0 (FGOALS-g3). The model datasets have been submitted to the Earth System Grid Federation (ESGF) node. Here, the details of the experiments, the output variables and some baseline results are presented. Compared with the preliminary results of other models, the evolutions of global mean variables can be reproduced well by FGOALS-g3. The simulations of spatial patterns are also consistent with those of other models in most regions except the North Atlantic and the Southern Ocean, indicating large uncertainties in the regional sea level projections of these two regions.

Erratum to: LICOM Model Datasets for the CMIP6 Ocean Model Intercomparison Project - Pengfei Lin; Zipeng Yu; Hailong Liu; Yongqiang Yu; Yiwen Li; Jinrong Jiang; Wei Xue; Kangjun Chen; Qian Yang; Bowen Zhao; Jilin Wei; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)

Comprehensive transcriptomics and proteomics analyses of rice stripe virus-resistant transgenic rice - Yang Xu; Lvjie Bi; Zipeng Yu; Chao Lin; Liming Gan; Lifei Zhu; Haiyang Li; Yunzhi Song; Changxiang Zhu (Journal of Biosciences, 2019)